2016
DOI: 10.1016/j.hlc.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging Predictors of Short-Term Outcomes after High Risk Coronary Surgery

Abstract: Cardiac magnetic resonance imaging preoperative LV and RV parameters are valuable in assessing the likelihood of successful outcomes from CAGS in high-risk patients with LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Accordingly, studies have suggested that presence of scar tissue after CABG is predictive of cardiac functional recovery. [51,52] Cardiac Magnetic resonance (CMR) imaging has become gold standard imaging technique for assessment of cardiac volumes, function and mass. Assessment of size and extent of scarring/fibrosis by Late Gadolinium Enhancement (LGE) has aided the detection and assessment of AMI.…”
Section: Significance Of Left Ventricular Contribution and Future Directions Of Cabgmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, studies have suggested that presence of scar tissue after CABG is predictive of cardiac functional recovery. [51,52] Cardiac Magnetic resonance (CMR) imaging has become gold standard imaging technique for assessment of cardiac volumes, function and mass. Assessment of size and extent of scarring/fibrosis by Late Gadolinium Enhancement (LGE) has aided the detection and assessment of AMI.…”
Section: Significance Of Left Ventricular Contribution and Future Directions Of Cabgmentioning
confidence: 99%
“…Sheriff et al observed a significant relationship between lower circumferential relaxation index (a CMR parameter) and the occurrence of immediate postoperative complications. [52] Thus, CMR would be suitable for use prior to CABG and provide additional prognostic information. Additionally, CMR can be used for monitoring assessing patient recovery process.…”
Section: Significance Of Left Ventricular Contribution and Future Directions Of Cabgmentioning
confidence: 99%